Pengaruh Mind Mapping Terhadap Hasil Belajar Mahasiswi Dalam Mata Kuliah Asuhan Masa Nifas Pada Prodi Kebidanan - Anieq Mumthi'ah Al Kautzar; Nurfaizah Alza (JIDAN (Jurnal Ilmiah Bidan), 2021)
Background: Learning outcomes are very important in the world of education because they are indicators of the achievement of planned targets. On learning of postnatal care is a comprehensive understanding is needed for female students. Models and methods of learning are very important for maximizing the achievement of learning goals. Mind mapping as one of the innovative learning methods that is expected to involve students to actively engage in learning, fun and interesting so as to improve concentration and memory. Purpose: to find out the effect of the application of mind mapping on the learning outcomes of students in the postnatal care of nursing study. Method: The research method used is quasi experiment with total sampling technique, the sample number of 74 respondents. The analysis used is paired t test and independent t test. Results: The results showed a meaningful increase in the average learning outcome between pretest and posttest in the intervention group by 12.63 and in the control group by 8.93 with a p value of 0.000(p < 0.05). There is a meaningful difference in the average learning outcome value between the intervention and control group of 3.70 with a p value of 0.000(p < 0.05) so it can be concluded that mind mapping affects the learning outcomes of students in the postnatal care course. Keywords: Mind mapping, Learning Outcomes, postnatal care